Legal interpretation will degrade president’s martabate and/vice president in achieving legal satisfaction - Tomy Michael; Abdul Rachmad Budiono; Moh. Fadli; Iwan Permadi (Technium Social Sciences Journal, 2020)
In the life of a state, legal certainty plays an important role because it’s interpreted as the strength of the real law. The existence of the principle of legal certainty is a form of protection for justice seekers against arbitrary actions, which means that a person will and can obtain something that is expected under certain circumstances. Based on the introduction, the formulation of the problem is whether the obscurity of the phrase “misconduct” contradicts Article 28D of the 1945 Constitution of the Republic of Indonesia concerning fair legal certainty and equal treatment before the law? This research uses legal research and uses a law approach and legal interpretation. In interpreting the phrase degrading the President and / or Vice President’s dignity, what is needed is an understanding of morals and moral awareness itself. This understanding is important to create good definitions and strengthen legal certainty.